Problem Based Learning Model with CRT Assisted by Augmented Reality to Improve Mathematics Learning Outcomes - Ihwan, Ahmad Zainal; Rusnilawati, Rusnilawati (Universitas Muhammadiyah Surakarta, 2025)
In the 21st century, educational innovations are essential to enhance student engagement and the relevance of learning materials to their cultural and technological contexts. This study investigates the effectiveness of the Problem Based Learning model integrated with the Culturally Responsive Teaching approach, supported by Augmented Reality media, on the mathematics learning outcomes of fourth-grade students at Banjarejo Elementary School, specifically in the topic of flat shapes. It also compares the learning outcomes between classes utilizing this innovative model and those employing conventional teaching methods. Employing a quantitative approach with a Quasi-Experimental design, the study involved two classes: IV A as the experimental group (N = 20) and IV B as the control group (N = 20). Research instruments included validated and reliable multiple-choice and essay questions. The independent t-test analysis revealed significant differences in learning outcomes between the two groups. The findings indicate that the PBL model combined with CRT and AR is effective, achieving an N-Gain value of 58.45%. This approach fosters contextual, interactive learning that aligns with students, cultural backgrounds, demonstrating its potential to enhance educational practices in mathematics.